Analisis Variabel-Variabel yang Mempengaruhi Kebijakan Dividen (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia) - Deni, Febrianto Frans; Aisjah, Siti; Djazuli, Atim (Universitas Brawijaya, Indonesia, 2016)
Abstract: This study aims to find out how Managerial Ownership, Institutional Ownership, Leverage, Company Size, Profitability, and Investment Opportunity influence on Dividend Policy. The population of this study is a manufacturing company that is listed on the Indonesia Stock Exchange Period 2007 to 2011 as many as 203 companies. This study used population criteria methodand obtained saturation samples from 32 companies. The data used are secondary data and methods of analysis is multiple regression analysis. The results showed that Institutional Ownership, Firm Size and Profitability has a positive influence, while Managerial Ownership has a negative but insignificant influence on dividend policy. Leverage has a negative influence while Investments Opportunity has a positive and significan influence on dividend policy. The conclusion of this study is a manufacturing company that has a high leverage will hold most of its earnings to repay debt and or for further fund projects so the company is able to maintain balance its capital structure in order to remain optimal. Manufacturing companies that have high profitability will provide a high dividend payments to give a signal to investors that the company foresees good profitability in the future